Behavior of Preventing Nutritional Anemia in Students Who Have Upper Arm Circumference (UAC) Below Normal - Hartati Bahar (Miracle Journal of Public Health, 2023)
The results of the 2018 Riskesdas showed that the incidence of anemia had increased from 2013, which was 37.1% to 48.9%. The increase in this figure is due to low nutritional status during pregnancy and improvement of the nutritional status can be started when they are teenagers or before pregnancy and marriage. The purpose of this study was to determine the behavior of preventing nutritional anemia in Public Health Faculty, Halu Oleo University students. This study used a descriptive research technique with a population of 42 female students with a sampling size of 30 samples. The sampling technique is simple random sampling. The target population is based on students who have Upper Arm Circumference (UAC) below normal as a risk factor for Chronic Energy Deficiency (CED) and anemia in adolescents. The results showed that there were 22 respondents who had sufficient knowledge (73.3%), 21 respondents who had a positive attitude (70.0%), and 20 respondents who had good actions (66.7%). The conclusion from this study was that students' knowledge was quite good but the proportion of poor anemia prevention measures was also still large, namely 33.3%.